Urban river revitalization at Sungai Batu downstream Sentul, Kuala Lumpur by using sustainable approach - Muhamad Tajuddin, Muhammad Hafizuddin (2018)
This study focuses on one of the major rivers in the Kuala Lumpur city which have experienced a deterioration in the quality of water and aquatic life caused by human activity around it. Formerly the river was one of the waterways and water sources to the local population, but the river's function had changed as the rapid development took place. The river's natural structure was renovated, concreted, and straightened in providing smooth rainwater runoff and the avoidance of flash floods. However, due to uncontrolled human activity and unplanned development, river water becomes dirty and polluted. Based on the site observation, residential, commercial and industrial areas are the major contributors to river pollution. In addition, river reserve of Sungai Batu downstream is lack of attraction and not well maintained. Hence, Sungai Batu downstream becomes a less-used area by local communities due to river water pollution, lack of pedestrian comfort and safety, and lack of public space attraction. Thus, this study aims on revitalizing Sungai Batu downstream into a vibrant community space through sustainable design approaches. Through this approach, Water Quality Index (WQI) of Sungai Batu downstream will increases and clean. It is also will provide public education to the community surrounding. The methodology of to undertake this study started with site observation and interviews with local communities, local authorities and daily workers. Then with information collected through secondary data sources, the data is analysed to form solution in term of synthesis and design strategies. Finally, the design details whereby the solutions are derived in term of space planning which is the master plan, perspective impression, and planting strategies. The result is a concise design completely satisfies human needs and environmental aspect. The use of overlaid mapping is the basis for defining design layouts that can help in generates the quality of life enhancement. In short, the sustainable design approach is one of the right choices in reviving the city's rivers and indirectly creating a livable communities in urbanized area.